Desenvolvimento e produção de quinoa sob irrigação e adubação potássica - Rêgo, Vanessa Mendes (2015)
Quinoa has high nutritional qualities, but conditions of low soil fertility can severely limit production, beyond his performance is hampered by the lack of water. Thus, the objective was to study the effect of irrigation levels and potassium fertilization in the development and production of quinoa in Oxisol. The experiment was conducted in greenhouse, located in UFMT, Campus Rondonopolis-Brazil, by using the soil collected from a Oxisoil Cerrado. The experimental design was a randomized block in a 5x5 factorial, with four replications, corresponding to five potassium rates (0, 100, 200, 400 and 600 mg dm-3 ) and five levels of irrigation (50, 75, 100, 125 and 150% field capacity), The evaluation were beginning from 15 days after seeding (DAS) plants, analyzing leaf area, stem diameter, chlorophyll index, leaf number and plant height and finished the 129 DAS collected dry mass of data shoot and root production and number of grains, mass of 100 grains and water use efficiency. The results had been submitted to the statistics analysis for the SISVAR program, determined it variance analysis and regression testing. There was a significant interaction between potassium and irrigation levels, only for the variable leaf area. The chlorophyll index, stem diameter and number of days for flowering were positively isolated response to potassium fertilization and irrigation levels. The dry matter of shoots and roots were influenced by potassium fertilizer in rates between 530 and 600 mg dm-3 . The irrigation levels and potassium fertilization between 99% to 104% and 350 to 373 mg dm-3 , respectively provide the maximum mass of grain yield and number of grains. The increase in irrigation levels reduces water use efficiency, already the potassium fertilization of 375 mg dm-3 provides maximum efficiency of this variable. Potassium fertilization and irrigation levels influence of isolation for all variables except for the leaf area showed that interaction between them.